Pengaruh Kegiatan Ekstrakulikuler terhadap Pengembangan Soft Skills Siswa - Wahyu Ardias; Khairul Fajri; Gusmanelli Gusmanelli (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The Influence of Extracurricular Activities on Increasing Students' Soft Skill Ability.This research is motivated by the results of observations that researchers made of students at SMKN 34 Jakarta which is very unfortunate because there are still many students at SMK Negeri 34 Jakarta who do not take part in extracurricular activities at all, even though there is very much that can be obtained if students take part in activities This is for example the ability of public speaking so that it supports students to be able to survive and develop in the world of work in the future. The method usedin this study is quantitative research using a correlational analytical descriptive approach, which combines the X and Y variables with a census of 17, which includes seventeen students.The results obtained from this study show that there is sufficient or moderate influence of extracurricular activities on improving the soft skills of students, the results of the analysis of the magnitude of the influence are 0.475 or 47%. The conclusion from the results of the analysis of the magnitude of the influence of extracurricular activities on improving soft skills of students is classified as sufficient or moderate, which is equal to 0.475 or 47%. This is because extracurricular activities are very influential in improving soft skills, soft skills are positive, the majority of students who take part in extracurricular activities well are students who have good soft skills too. meaning that there is an influence of extracurricular activities on the improvement of students' soft skills.